PENGARUH PEMBERIAN ZEOLIT TERHADAP EFISIENSI PEMUPUKAN FOSFOR DAN PERTUMBUHAN JAGUNG MANIS DI PASURUAN, JAWA TIMUR - Yasir Arafat; Novalia Kusumarini; S Syekhfani (Jurnal Tanah dan Sumberdaya Lahan, 2016)
The purpose of this study was to show effects of  zeolit application toward efficiency of P fertilizer, P absorbtion and sweet corn growth. This study was conducted at farmer’s land in Bugul Kidul Sub District, Pasuruan of East Java. This study used a randomized block design consisting of twelve treatments with three repetitions. The treatments tested were 0 t zeolit ha-1 (A0),  4.65 t zeolite  ha-1 (A1), 9.3 t zeolite ha-1 (A2), 0 kg SP-36 fertilizer ha-1 (F0), 75 kg SP-36 fertilizer ha-1 (F1), 150 kg SP-36 fertilizer ha-1 (F2), and 225 kg SP-36 fertilizer ha-1 (F3). The results showed that zeolite influenced the efficiency of P fertilization. The extending of 9.6 t zeolite ha-1 with combination of 150 kg SP-36 fertilizer ha-1 had efficiency of P fertilization of 65 %. The utilizing of 9.3 t zeolite ha-1 and 150 kg SP-36 fertilizer ha-1 increased plant height up to 34.8 %, plant fresh weight increased up to 95.7 % and plant dry weight up to 98 %. Those results showed that application of zeolite improved P fertilization efficiency, P absorbtion and sweet corn growth